Primary Malignant Melanoma of the Tonsil : A Case Report - Badruddoza, SM; Naz, S (TAJ: Journal of Teachers Association, 2009)
Malignant melanoma is a neoplasm of melanocytes. Primary malignant melanoma of the oronasal region is rare. When it does occur, it is difficult to manage, and the prognosis is not good. The current case was a 48 years old male patient who presented with history of sore throat, pain in left tonsillar region, hemoptysis with difficulty in swallowing. Clinical examination revealed a blackish ulcerated polypoid mass in the left palatine tonsil. Left sided tonsilectomy was done. Histopathological examination revealed primary malignant melanoma of the tonsil. TAJ 2009; 22(1): 279-281